Does categorisation of lymphoma subtypes according to the World Health Organization classification predict clinical outcome in cats?. Issue 8 (August 2017) - Wolfesberger, Birgitt; Skor, Ondrej; Hammer, Sabine E; Flickinger, Irene; Kleiter, Miriam; Rütgen, Barbara C; Schwendenwein, Ilse; Tichy, Alexander; Hittmair, Katharina M; Degasperi, Brigitte; Fuchs-Baumgartinger, Andrea
Objectives: The purpose of this study was to specify lymphoma subtypes according to the World Health Organization (WHO) classification in a group of cats and to investigate their potential prognostic value. Methods: Records of cats from the University of Veterinary Medicine Vienna suffering from lymphoma were reviewed in this retrospective study. To diagnose various subtypes specified in the WHO classification, histopathological and immunohistochemical examinations, as well as clonality assays in some cases, were performed. Results: Of the 30 cats included in this study and classified according to the WHO guidelines, peripheral T-cell lymphoma was the most prevalent lymphoma subtype (37% of cases; n = 11), followed by diffuse large B-cell (23%; n = 7), intestinal T-cell (10%; n = 3), T-cell-rich B-cell (10%; n = 3), large granular lymphocytic (7%; n = 2), anaplastic large T-cell (7%; n = 2), B-cell small lymphocytic (3%; n = 1) and T-cell angiotropic lymphoma (3%; n = 1). The median survival time (MST) was 5.4 months (range 6 days to 2.2 years), with two cats still alive after 1.7 and 2.0 years, respectively. Treating cats prior to chemotherapy with glucocorticoids did not worsen their prognosis. Adding to chemotherapy, radiotherapy or surgery did not improve the clinical outcome. We observed that patients with intestinal T-cell lymphoma lived significantly longer (MST 1.7 years) than those with a diffuse large B-cell (MST 4.5 months) or peripheral T-cell lymphoma (MST 6.1 months). Cats with T-cell-rich B-cell lymphoma survived significantly longer (MST 1.2 years) than those with a diffuse large B-cell lymphoma. Conclusions and relevance: A detailed diagnosis of feline lymphoma can be obtained by allocating different subtypes according to the WHO classification. From the eight detected lymphoma subtypes, two, intestinal T-cell lymphoma and T-cell-rich B-cell lymphoma, showed promising survival times in cats.